Evolution of the institutional characteristics of the first university of Belarus under the political and economic strengthening of the Belarusian statehood (1919–1925) - Yanouski, Aleh A. (Journal of the Belarusian State University. History, 2023)
On the basis of new archival data, the process of consolidating the most important institutional characteristics (staffing, organisational forms of training and research, structural features, etc.) of the first university of Belarus – the Belarusian State University is considered. This process reflects the institutional evolution of the institution of higher education. The evolution of university institutionalism is considered against the background of the political and economic strengthening of the Belarusian statehood, the practice of its relations with the RSFSR (USSR). The difficulties that both the state and its university had to overcome on the way to achieving, if not complete independence, then equality in the conditions of initially shaky ideas in the political environment and public perception of the historical self-sufficiency of Belarusians are shown.
Keywords: Belarusian State University; Belarusian statehood; institutional characteristics; RSFSR; USSR; policy; economics; forms of interaction